Identification of fatty acid methyl ester in palm oil using gas chromatography-mass spectrometer - Sulaiman, Sarina (Springer Nature, 2018)
Biodiesel or Fatty Acid Methyl Ester (FAME) is a non-toxic, biodegradable alternative fuel that is easy to produce and process from vegetable oil or animal fats. In this chapter, identification of Fatty Acid Methyl Ester in palm oil biodiesel using GCMS has been studied. The main component existed in FAME are Caprylic acid C8:0, Capric acid C10:0, Myristic acid C14:0, Palmitic acid C16:0, Stearic acid C18:0, Oleic acid C18:1, Arachidate acid C20:0 and Docosanoic acid C22:0.